Agricultural Credit Policy and Livestock Development in Nigeria - Sunday Akpan; Veronica Nkanta; Edet Udoh (Zeszyty Naukowe Szkoły Głównej Gospodarstwa Wiejskiego w Warszawie. Problemy Rolnictwa Światowego, 2023)
This research aimed to provide empirical information on the relationship between the livestock production index and the credit policy environment in Nigeria. Time series data were used, and an autoregressive distributed lag (ARDL) bound test approach was adopted to establish the presence of co-integration among series. The estimated long and short run models showed stability, best quality, efficiency and unbiased. The findings showed that in the long run, total credit to the agricultural sector from commercial banks and domestic credit to the private sector both had significant positive influence on livestock production, while agricultural credit guarantee scheme loans to livestock units exhibited a negative impact. In the short run, agricultural credit guarantee scheme loans to livestock, lending interest rate, and domestic credit to the private sector negatively relate to livestock production. However, the commercial banks’ total credit to the agricultural sector showed a positive effect on livestock production in the short run. The implication of the findings indicates a need to increase total commercial credit to the agricultural sector and domestic credit to the private sector, to reassess the agricultural credit guarantee scheme, and to lower the lending interest rate for agricultural credit – these as a means for increasing livestock production in the country.